The intervention of local public authorities and the impact of the COVID-19 pandemic in Romania: a subnational analysis - Ștefan, George; Bodislav, Dumitru Alexandru; Arsăni (Chiriță), Alina; Hrebenciuc, Andrei; Paierele, Ada; Paraschiv, Anca; Virjan, Daniela (Frontiers in Public Health, 2024)
The COVID-19 pandemic had a strong territorial dimension, with a highly asymmetric impact within counties, depending on pre-existing vulnerabilities, regions’ economic structure, exposure to global value chains, specialization, and overall ability to shift a large share of employees to remote working. The aim of this paper is twofold: (i) to assess the role of Romanian local authorities during this unprecedented global medical emergency by capturing the changes of public spending at the local level between 2010-2021 and amid the COVID-19 pandemic, and (ii) to identify clusters of Romanian counties that shared similar characteristics in this period, using consequently both a panel data and hierarchical cluster analysisThe topic is particularly relevant for Romania, and it requires further reflection as according to international organizations to increase its local resilience to be better prepared for future shocks and to implement evidence-based public policies.